PENGARUH BEBAN KERJA DAN DUKUNGAN SOSIAL TERHADAP KINERJA PEGAWAI PADA PT. BPR BANK DAERAH GIANYAR (PERSERODA) - Putu Melisa Dewi Jayanti; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
The importance of improving employee performance will bring progress to the organization to be able to provide satisfactory services. Therefore, efforts to improve employee performance are a very serious challenge for every company. Increasing performance is the responsibility of an employee, one of which can be a work target and the working hours charged. This study aims to determine the effect of workload and social support on employee performance at PT. BPR Regional Bank of Gianyar (PERSERODA). This research was conducted at the office of PT. BPR Regional Bank of Gianyar (PERSERODA) having its address at Jalan Ngurah Rai no 71 Gianyar, with the object of research being Workload and Social Support on Employee Performance. The population in this study were employees at PT. BPR Regional Bank of Gianyar (PERSERODA) totaling 40 people. The sample of this study was determined by the population method, so the number of samples was 40 people. Data analysis in this study used the SPSS version 23.0 application. The data analysis technique used is validity test and correlation coefficient value (r) > 0.30, reliability test with Cronbach Alpha > 0.60, multiple linear regression analysis. In addition, in this study, classical assumption tests were also carried out which included tests of normality, multicollinearity, and heteroscedasticity. The results of this study indicate that the workload has a negative effect on the performance of employees of PT. BPR Regional Bank of Gianyar (PERSERODA). Social support has a positive effect on employee performance at PT. BPR Regional Bank of Gianyar (PERSERODA).